The use of an improvised Nasogastric Tube as a Peritoneal Dialysis Catheter and challenges of adaptation-A case report (2019)
Background: Paediatric dialysis for acute kidney injury (AKI) in developing countries may be a challenge because of limited access to standard gadgets. Adapted gadgets such as nasogastric tubes have been used to provide peritoneal dialysis (PD)in such settings. The nasogastric tube is usually inserted by the trocar or surgical technique which is cumbersome. We describe passage of the nasogastric tube for PD at the bedside by a technique that is considered easier than the trocar or surgical method. Case report and Treatment: A two- and-a-half-year-old girl presented with oliguric AKI secondary to malaria and intravascular haemolysis with suspected uraemic encephalopathy. Her serum creatinine on admission was 9.4mg/dl. A nasogastric tube was adapted as PD catheter, and was inserted by the modified Seldinger technique on post-admission day 1. Results: She received 39 cycles of PD over 5 days. Complications of PD included catheter outflow obstruction on post admission day 2 on account of which the catheter was replaced. She also developed Klebsiella pneumoniae peritonitis and on account of which the procedure was discontinued on post admission day 6. She regained normal urine output on post admission day 7. She was managed with iv meropenem based on the antibiotic sensitivity pattern with resolution of peritonitis. She showed significant improvement and her serum creatinine on post admission day 15 was 0.5 mg/dl.She was discharged home on post admission day 18. Conclusion: Nasogastric tube, adapted as PD catheter and inserted by modified Seldinger technique may be life-saving in patients with AKI in developing countries.